Molecular characterization and homology modeling of a short-chain reductase/dehydrogenase from Gracilaria changii (Rhodophyta) - Naseron, Nur Anisza Hanoum; Lim, Kok Ang; Teh, Seow Ling; Teo, Swee Sen; Leow, Adam Thean Chor; Namasivayam, Parameswari; Ho, Chai Ling (Springer, 2014)
Short-chain dehydrogenases (SDRs) which catalyze the dehydrogenation/reduction reaction have a wide range of substrate specificities. In this study, we report the molecular characterization of a transcript encoding SDR from the red seaweed, Gracilaria changii (Rhodophyta) as part of our effort to elucidate the functions of novel transcripts from this marine alga. The transcript, denoted as GcSDR, encodes a protein of 282 amino acids with a predicted size of approximately 31 kDa. The GxxxGxG coenzyme binding motif and YxxxK active-site motif of SDRs are well conserved in GcSDR. The coding sequence of GcSDR was cloned and expressed as recombinant protein in Escherichia coli BL21 (DE3) pLysS. Kinetic analysis of recombinant GcSDR using pyruvaldehyde dimethyl acetal as a substrate has a Km value of 116.52 mM and a Vmax value of 720 nmol product formed per minute per milligram. It has a higher affinity towards NADPH compared to NADP+ as a cofactor. Homology modeling showed that the three-dimensional structure of GcSDR has 34.5 % sequence identity to the SDR from a soil bacterium. Virtual screening of the possible substrates for GcSDR revealed that CMP-N-acetyl-beta-neuraminate (2-) which belongs to a group of amino sugars has the lowest binding energy among the compounds examined. The predicted cis-acting regulatory elements (CREs) at the 5′-flanking genomic sequence of GcSDR include CREs associated with abscisic acid, methyl jasmonic acid, light, anoxia, endosperm, low-temperature stress, and heat stress. The transcripts of GcSDR were found to accumulate in seaweed samples treated under low-salinity stress, thus suggesting its involvement during saline deprivation.